The Perpetual Trouble with Network Products Why IT Firms Choose Partial Compatibility - Manfred Stadler; Céline Tobler Trexler; Maximiliane Unsorg (Networks and Spatial Economics, 2022)
Compatibility of network products is an important issue in markets for communication technology as well as hard- and software products. Empirical findings suggest that firms competing in these markets typically choose intermediate degrees of product compatibility. We present a strategic two-stage game of two firms deciding independently or commonly on the degree of product compatibility in the first stage and on prices in the second stage. Indeed, partial compatibility constitutes a subgame perfect Nash equilibrium when coordination costs of standardization are high and the installed bases are low - conditions that typically characterize IT markets.
Keywords: C72; L13; L15; 000; Network products; Network effects; Compatibility